Diagnosis of pulmonary hypertension in the congenital heart disease adult population impact on outcomes - Lowe, Boris S; Therrien, Judith; Ionescu-Ittu, Raluca; Pilote, Louise; Martucci, Giuseppe; Marelli, Ariane J (Journal of the American College of Cardiology, 2011)
The aim of this study was to assess the impact of the diagnosis of pulmonary hypertension (PH) on mortality, morbidity, and health services utilization (HSU) in an adult congenital heart disease (CHD) population. Although PH is a well-recognized complication of CHD, population-based studies of its significance on the survival and functional capacity of patients are uncommon. A retrospective longitudinal cohort study was conducted in an adult CHD population with 23 years of follow-up, from 1983 to 2005. The prevalence of PH was measured in 2005. Mortality, morbidity, and HSU outcomes were compared between patients with and without diagnoses of PH using multivariate Cox (mortality and morbidity) and Poisson (HSU) regression models within a subcohort matched for age and CHD lesion type. Of 38,430 adults alive with CHD in 2005, 2,212 (5.8%) had diagnoses of PH (median age 67 years, 59% women). The diagnosis of PH increased the all-cause mortality rate of adults with CHD more than 2-fold compared with patients without PH (hazard ratio [HR]: 2.69; 95% confidence interval [CI]: 2.41 to 2.99). Morbid complications including heart failure and arrhythmia occurred with a 3-fold higher risk compared with patients without PH (HR: 3.01; 95% CI: 2.80 to 3.22). The utilization of inpatient and outpatient services was increased, especially cardiac catheterization, excluding the index diagnostic study (rate ratio: 5.04; 95% CI: 4.27 to 5.93) and coronary and intensive care hospitalizations (rate ratio: 5.03; 95% CI: 4.86 to 5.20). A diagnosis of PH in adults with CHD is associated with a more than 2-fold higher risk for all-cause mortality and 3-fold higher rates of HSU, reflecting high morbidity.